Taxonomy of the genus Kochogaster Kamiński et Raś, 2011 (Coleoptera: Tenebrionidae: Pedinini), with description of a second known species - Kamiński, Marcin Jan; Iwan, Dariusz (Zootaxa, 2013)
A second species of the genus Kochogaster Kamiński et Raś (K. gerardi sp. n.) is described from the surroundings of Ga-rissa (Kenya). The taxonomic concept and phylogenetic relationships of Kochogaster are discussed. A distributional map is presented with complete faunistic data on the genus. Additionally, the original spelling of the name Anchophthalmus muelleri Schimrosczyk, 2010 is emended to A. muellerae due the rules of the International Code of Zoological Nomen-clature.